Reevaluating the Role of Bronchoscopy Prior to Bronchial Artery Embolization in Nonintubated Patients With Hemoptysis Due to Bronchiectasis and Chronic Pulmonary InfectionTake-Home Points - Takashi Nishihara, MD; Hideo Ishikawa, MD; Kazunari Tsuyuguchi, MD, PhD; Shoichi Fukuda, MD, PhD; Hiromitsu Sumikawa, MD, PhD (CHEST Pulmonary)
Background: When performing bronchial artery embolization (BAE), identifying the side of bleeding and thereby deciding the side of embolization is crucial for an effective and safe procedure. However, there is little evidence regarding the utility of bronchoscopy for determining the side of embolization prior to BAE in nonintubated patients with hemoptysis admitted to general wards. Research Question: Is bronchoscopy necessary prior to BAE in nonintubated patients with hemoptysis following bronchiectasis and chronic pulmonary infection? Study Design and Methods: Data from 93 consecutive nonintubated general ward patients with bronchiectasis and chronic pulmonary infection (nontuberculous mycobacteriosis, aspergillosis, and TB) who underwent de novo BAE from September 2017 to August 2023 were retrospectively reviewed. The contribution of bronchoscopy in deciding the side of embolization was evaluated. Results: All patients underwent CT imaging and 27 also underwent bronchoscopy. Bronchoscopy identified the sides of bleeding in 9 patients, but these sides could be correctly estimated in 8 of them from the CT information alone. Bronchoscopy did not reveal the side of bleeding in 18 patients, whose sides of embolization were decided using CT imaging and angiographic information. Of 66 patients without bronchoscopy, the sides of embolization were decided in 63 patients using CT imaging and angiographic information, but the priority of the embolization side could not be decided in the remaining 3 patients. Overall, 96% (89 of 93) of patients did not require bronchoscopy as part of their embolization plan. The 90-day overall survival and hemoptysis-free survival rates were 98.9% (95% CI, 92.5-99.8) and 92.3% (95% CI, 84.6-96.3), respectively. Interpretation: This study showed that bronchoscopy contributed little to the planning of BAE in nonintubated patients with hemoptysis following bronchiectasis and chronic pulmonary infection. Our findings do not support the routine use of bronchoscopy prior to BAE in this population.